Observing the magnetization reversal processes and anisotropic effective damping of epitaxial FeSi/MgO (001). (13th January 2021) - Guo, X B; Jiang, Y P; Lu, X L; Tang, X G; Tang, Z H; Liu, Q X; Li, W H; Zuo, Y L; Xi, L
Abstract: Epitaxial FeSi film on MgO (001) substrate was fabricated via a radio frequency magnetron sputtering technology. The epitaxial relationship of FeSi(001)/[110]//MgO(001)/[100] was characterized by crystal structure measurements and confirmed by in-plane biaxial magnetic anisotropy through vibrating sample magnetometer (VSM). By measuring Kerr magnetic hysteresis loops and recording the real-time magnetic domain images through surface magneto-optic Kerr effect (MOKE), two successive 90° domain wall displacement along easy axis and two discontinuous 90° domain wall displacement along hard axis were directly observed. Meanwhile, the difference of magnetic hysteresis loops obtained by VSM and MOKE devices were discussed. Furthermore, from the results of magnetic field sweeping ferromagnetic resonance measurements, it was found that FeSi film possesses an anisotropic effective damping constant of 0.0042 for easy axis direction and 0.0053 for hard axis direction, which was ascribed to the crystallographic defects induced two magnon scattering contributions.